Otimização discreta por nuvem de partículas aplicada ao problema do caixeiro viajante - Aloise, Dario José; de Oliveira, Marilyn Cristine; Silva, Thales Lima (Revista Gestão da Produção Operações e Sistemas, 2006)
Particle Swarm Optimization (PSO) is a metaheuristic that originated from the intention to simulatethe behavior of a flock of birds in locally random, but globally determined movement. This technique has beenwidely used in the resolution of non-linear continuous problems and is still not explored enough for theresolution of discrete problems. This paper presents the performance of this metaheuristic with new adaptationsfor its application to discrete optimization problems. Results of computational experiments are presented forsome instances of the travelling salesman problem chosen in the TSPLIB, to demonstrate the efficiency of theadapted method in the resolution of problems of this category.Keywords: Particle Swarm Optimization; Global Optimization; Combinatorial Optimization.